Passover as "Passion": A Folk Etymology in Luke 22,15 - Reece, Steve (Biblica, 2019)
Great significance is attached to the etymologies of proper names in the Hebrew Scriptures, in the Greek New Testament, and in ancient Greek and Latin literature generally. The author of Luke-Acts embraces this literary tradition, offering several subtle and sophisticated etymological wordplays on proper names for persons and places: Barnabas, Barjesus, Jesus, and Gaza. One that has been entirely overlooked is his etymological wordplay on the Hebrew festival name("Passover"), which he associates with the Greek verb("to suffer"). This is not just a casual wordplay introduced as a literary device; rather, this etymological wordplay reinforces an important leitmotif that runs through the entirety of Luke-Acts: that Jesus is the new Passover lamb (Πάσχα) through whose suffering (πάσχω) salvation is offered to all.